Mitigating Fraud in Uganda’s Digital Land Registry System: A Case Study of Kampala and Mukono Districts - Joshua Morris Byaruhanga (Uganda Christian University, 2024)
Digitalization is a prevailing global phenomenon as countries endeavour to transition to digital platforms to enhance the effectiveness of existing systems. This research delves into the issue of fraudulent activities in land transactions within the digital land registry system in Uganda, specifically in the Kampala and Mukono districts. The study meticulously examines the theoretical framework of land ownership in Uganda, drawing from historical concepts such as the Torrens system of land registration and the persistent challenge of fraud faced by this system. The research reveals that fraud has been a pervasive and enduring problem in land ownership in Uganda. This issue has been recurrent in the country, with the only existing defence against fraudulent land transactions being the bona fide purchaser for value without notice, which was a central focus of the study. Furthermore, the study explores the mechanisms that have been implemented to combat fraud in land transactions in Uganda, particularly through the establishment of the digital land registry system by the Ministry of Lands, Housing, and Urban Development in collaboration with IGN - France and the World Bank in 2013, as a strategy to mitigate fraudulent activities. An analysis of the challenges associated with digitalization of land records in Uganda is provided, highlighting the initial efforts made by the Ministry of Lands and Urban Development in setting up the Digital Land Registry system. A comparative analysis is then conducted to assess the state of digitalization of land records in Uganda against other digital land registry systems, such as the Ardhi Sasa in Kenya and the Ubutaka in Rwanda, along with the challenges faced by these systems. This serves as a valuable tool to evaluate the efficiency of Uganda’s Digital Land Registry System. The study concludes that Uganda’s Digital Land Registry System is currently ineffective due to various challenges, including the failure to fully digitize the entire land transaction process, resulting in only 1% of the process being conducted on-line. Recommendations are put forth to the Government of Uganda, under the Ministry of Lands, Housing, and Urban Development, to enhance the digital land registry system. These recommendations include raising public awareness about the digital land registry and ensuring that 90% of land sale transactions are conducted through the system.